Desire-satisfactionism and the no-future time of desire view - Choo, Frederick Wen Yeong (2019)
Desire satisfactionism states that a person’s well-being increases when one’s desires are satisfied, where one’s desires are satisfied if the desired object obtains. A person can have a desire at a certain point of time but the desired object may only obtain at another time where the person lacks the desire. This raises two questions. First, does a person benefit when the desire and the desired object do not temporally overlap? Second, at what time, if any, does a person benefit in such cases? This paper advances a new view called No-Future Time of Desire. This view says that a person does not benefit if the desired object obtains after the desire, though a person can benefit if the desired object obtains prior to the desire. In such cases, a person benefits at the time they have the desire. I argue that this view is superior to other current views such as Time of Desire, Time of Object, Asymmetrism, Fusion and Concurrentism.